Variability of N-SPT-Correlated Undrained Shear Strength of Alluvial Deposit in Doplang Region, Central Java, Indonesia - Sugeng Krisnanto; Masyhur Irsyam; Rendy Dwi Kartiko; Arif Rahman Hakim Sitepu; Mohammad Anwar Fathoni; Ina Asha Nurjanah; Shafira Annisa Putri; Lindawati Lindawati; Maudy Anisa Fanani; Alexander Wicaksono Budiarto; Idrus Muhammad Alatas (Directorate for Research and Community Services, Institut Teknologi Bandung, 2023)
The need to better quantify the variability of soil shear strength and its relations with the factor of safety is increasing in Indonesia. However, this aspect has not yet been studied thoroughly. This paper presents an attempt to quantify the variability of undrained shear strength in relation with the factor of safety of an alluvial deposit in the Doplang region, Central Java, Indonesia. A relationship between the undrained shear strength, su, and N-SPT for the deposit was found as su = 3.4 N-SPT. The variability of the undrained shear strength was quantified utilizing the coefficient of variance, s/m (the sample standard deviation, s over the mean, m) of the N-SPT correlated undrained shear strength. The variability of the undrained shear strength was investigated for the soil near ground surface. The deposit had a value of s/m ranging from 0.15 to 0.25 near ground surface. The variation of s/m tended to follow normal and lognormal distributions. Relationships among the coefficient of variance, the probability of failure, and the factor of safety in terms of soil strength for normal and lognormal distributions were developed. For the value of s/m near ground surface, the relationship between the probability of failure and factor of safety was obtained.